Determinasi Adopsi ShopeePay di Kalangan Generasi Z Melalui Kemudahan Sistem, Proteksi Transaksi, Pola Gaya Hidup, dan Kapabilitas Literasi Keuangan - Mutiara Lusiana Annisa; Guntoro Barovih; Fahmi Ajismanto (INDO PUBLISHING, 2026)
This study examines the determinants influencing ShopeePay adoption among Generation Z, focusing on system usability, transaction security, digital lifestyle, and financial literacy. Data were collected from 75 Generation Z ShopeePay users residing in Palembang City through an online questionnaire, using non-probability sampling with an incidental approach. The findings reveal that system usability has a positive but statistically insignificant effect on ShopeePay adoption, whereas transaction security, digital lifestyle, and financial literacy demonstrate positive and significant influences, with digital lifestyle emerging as the most dominant factor. These results are expected to contribute to the literature on digital finance and consumer behavior, particularly in understanding e-wallet adoption among Generation Z.